Program Kampung Berdaya dalam Meningkatkan Partisipasi Masyarakat Menuju Kesejahteraan - Nenden Rhesi Latifatul Karimah; Deden Sumpena (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to find out how the Berdaya Foundation approach, the form of participation and the results of participation obtained by the Patrol Village community with the Kampung Berdaya program. The method in this study is a qualitative method with a descriptive approach. Data collection techniques through interviews, observation, and documentation. The results of the study are: the approach taken by the Berdaya Foundation using the PRA (participatory rural appraisal) technique. Forms of community participation, namely: the participation of ideas, energy, property, skills / skills and social. The success of community participation is to increase the welfare of the patrol village community in terms of health, education, economy and social aspects.